A Rare Case of Syringomatous Tumor of the Nipple and Breast Reconstruction - Araújo, Juliana Lopes de Aguiar; de Sousa, Ubiratan Wagner; Dantas, Macerly Laise de Menezes; Pimper, Waleria; Navarro, Diana Taissa Sampaio Marinho (Mastology, 2024)
Syringomatous tumor, first described in 1983, is a rare benign clinical condition that can affect the breast. Its infiltrative form is often misidentified as malignant pathologies, as it can present as a subareolar lesion with suspicious clinical, mammographic, and ultrasound findings for malignancy. The exact origin of these lesions remains uncertain; however, they may manifest as a unilateral or bilateral subareolar nodule with symptoms such as pain, edema, nipple enlargement, and nipple discharge. Despite local infiltration, there is no evidence of regional or distant metastases. Local complete excision appears to be an adequate therapy, with only cases that were incompletely excised showing recurrence. Below is a case report of a syringomatous adenoma infiltrating the nipple, with complete resection and nipple reconstruction using oncoplastic techniques.